Laboratory Study of Enhanced Oil Recovery with Used Palm Oil Surfactant Injection - Puri Wijayanti; Nandito Davy; Onnie Ridaliani; Pauhesti; Samsol; Widia Yanti; Tia Agusta; Rizka Nada Setyani (Journal of Earth Energy Science, Engineering, and Technology, 2023)
Currently the waste generated from public consumption in Indonesia is very high. One such waste is used palm oil from households and food companies. Utilization of this waste in this research is by recycling waste oil into surfactants which will be used in the Enhanced Oil Recovery (EOR) process. The surfactant concentrations used were 1.3%, 1.5%, 2%, 2.2% and 2.5%. The research began with refining used cooking oil with banana peels for 24 hours. In order to make surfactants, the oil is mixed with KOH and distilled water. Additionaly, brine was made with a salinity of 15,000 ppm. With the interfacial tension test, a solution with an optimum surfactant concentration of 2.2% was obtained. The core flooding test was carried out using waterflooding followed by surfactant flooding at a temperature of 70 oC. From the test results obtained an incremental oil recovery factor of 8.57% and a total oil recovery factor of 47.43%.